Sacrum in the Age of its Mechanical Reproduction - Sodeika, Tomas (Religija ir kultūra, 2010)
In his essay “The Work of Art in the Age of Mechanical Reproduction” Walter Benjamin discusses a loss of the aura through the rise of photography and cinema. The notion of aura for Benjamin represents the originality and authenticity of a work of art that has not been reproduced. But at the same time it represents connection of the realm of art to the experience of the sacrum. The article deals with the correlation between the loss of aura and the desacralisation of the contemporary world.
Keywords: desacralisation; Walter Benjamin; media